Stock market return predictability: Google pessimistic sentiments versus fear gauge - Ume Habibah; Suresh Rajput; Ranjeeta Sadhwani (Cogent Economics & Finance, 2017)
This study aims at comparing Google Search Volume Indices (GSVIs-including market crash and bear market) and VIX (Investor Fear Gauge Index) in terms of explaining the S&P 500 returns. The VIX is found a more robust predictor of stock market returns than Google indices, and it does granger cause the GSVIs more robustly. In addition, in vector auto-regression model, VIX has more prominent effect of its past values on both Google indices. Finally, using the autoregressive distributed lag (ARDL) and nonlinear ARDL models, contrary to prior literature, we find significant symmetric negative relationship between changes in VIX and S&P 500 returns.
Keywords: C22; G02; G12; 330; investors'pessimistic sentiments; Google Search Volume; ARDL; NARDL; stock market returns; volatility index